Persistent inequities in neonatal encephalopathy: a 30-year global burden analysis (1990–2021) - Yuan, Yiming; Zhao, Mingyue; Zhi, Jincao; Guo, Zinan; Dong, Jianyang; Tian, Xiaoying; Feng, Lin; Wang, Yan (Frontiers in Pediatrics, 2026)
BackgroundNeonatal encephalopathy (NE) remains a significant cause of mortality and long-term disability in children under five, with pronounced global disparities in incidence and outcomes despite available interventions. This study aims to identify inequalities in the NE burden, with the goal of informing strategies to promote health equity and well-being in children.MethodsUsing data from the GBD 2021 study, we analyzed NE incidence, mortality, and disability-adjusted life years (DALYs) across 204 countries from 1990 to 2021. Data were assessed by age, sex, region, and Sociodemographic Index (SDI). Trends were quantified using estimated annual percentage change (EAPC).ResultGlobally, NE incidence declined by 18.1%, mortality by 31.6%, and DALYs by 27.7% from 1990 to 2021. Males had a higher burden. A substantial disparity was observed: the age-standardized mortality rate in low-SDI regions was 22 times that of high-SDI regions. Western Sub-Saharan Africa and South Asia carried the highest burden. Low birth weight accounted for 58.4% DALYs of NE globally, with a disproportionate effect in low- and middle-SDI regions.ConclusionDespite an overall reduction in the global NE burden, it remains disproportionately concentrated in resource-limited settings. Persistent disparities in low- and middle-SDI regions necessitate urgent, targeted interventions—including scaled-up perinatal care, strengthened health infrastructure, and region-specific strategies—to mitigate inequities. Middle- to high-SDI countries must address evolving epidemiological patterns. Equitable expansion of rehabilitation resources is critical to improving long-term outcomes and reducing disease burden.